Assembly the Semantic Cultural Heritage Knowledge - Pramartha, Cokorda Rai Adi (Jurnal Ilmu Komputer; Vol 11 No 2 (2018): Jurnal Ilmu Komputer, 2018)
This project aims to assembly the semantic cultural heritage knowledge dealing with one aspect of Balinese heritage, the kulkul system. We discuss our method and procedures to realize the goal of the project. The significant contribution of cultural heritage expert resulted in the kulkul specification and features. Also, the involvement of a knowledgeable community helped us to expand and validate the kulkul ontology. Finally, the cultural heritage knowledge was made available in the form of ontology to represent the knowledge that can be processed and manipulated by the computer program.